Kierunki integracji systemów informacyjnych zarządzania - Sierocki, Robert (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Information systems integration is a vital problem when assurance of appropriate IT efficiency level is considered. The article presents review of information systems integration definitions and synthesis of current trends. The author emphasizes current direction of IT with business integration where enterprise information system architecture seems to be a significant tool. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 89-102